HUBUNGAN PENGETAHUAN IBU DAN DUKUNGAN KELUARGA SEPUTAR PEMBERIAN ASI DENGAN STATUS GIZI ANAK USIA PRASEKOLAH DI TK ISLAM NURUL QURAN - Siti Juhariyah (2022)
The nutritional status of children can be influenced by food, health conditions, parenting patterns, as well as health and environmental services. This study aims to determine whether there is a relationship between mother's knowledge and family support regarding breastfeeding with the nutritional status of preschool-aged children in Nurul Quran Islamic Kindergarten. The method used is observational analytic with a total sampling technique of 48 mothers and children aged 4-6 years. Univariate analysis using proportion test and bivariate analysis using Kendall's tau b test. The results of this study indicate that there is a significant relationship between the level of mother's knowledge about breastfeeding and the nutritional status of preschool-aged children, namely with a p-value = 0.000, and there is a significant relationship between family support regarding breastfeeding and the nutritional status of preschool-aged children, namely the p-value value = 0.026. It is hoped that mothers can participate in training and socialization about the nutritional status of children in order to understand the correct and appropriate nutritional intake according to the needs of children. Mothers should check the condition of the child's nutritional status regularly. Families should be able to provide support and attention to mothers so that mothers are motivated to provide balanced nutritional intake to children.